Do Good Governance Business Sharia, Innovation and Financial Performance Affect Islamic Social Reporting Quality? - Tri Wahyu Oktavendi; Fahmi Dwi Mawardi (Jurnal Akademi Akuntansi, 2023)
Islamic Social Reporting is an important aspect for companies with sharia principles in increasing their value. Reporting Disclosure currently only focuses on quantity not quality. Quantity can cause information anomaly because it is only based on the amount of disclosure, the way to minimize it is to focus on the quality of social Islamic disclosure. The purpose of this study was to analyze empirically the effect of financial performance (ROA), Innovation Disclosure (ID) and Good Governance Business Sharia (GGBS) on Islamic Social Disclosure (ISR). This study uses moderated regression analysis (MRA) with e-views 11. The sample used is a banking company registered with the financial services authority (OJK). The results of this study indicate that ROA has no effect on ISR, while the other variables, namely ID and GGBS, have an effect on ISR. The results of this research have practical implications, namely the practice of sharia governance and innovation is a part that needs to be strengthened to encourage management to improve the quality of ISR disclosure. In terms of theoretical implications, the results of this research become literature that can contribute to the development of the ISR research model.